Beauveria bassiana PATHOGENICITY (bals) vuill., The SCREWWORN LOCHE Diaphania hyalinata (Lepidoptera: Pyralidae) IN LABORATORY - Lloclla Gonzales, Herry (2017)
Diseases caused in many insects by parasites knowns as Entomopathógenic fungi composes an ecological alternative in the pest management in different agricultural crops. The patogenicity of the Beauveria bassiana was established in this present study as an important crop pest due to its potential application as microbiological control agent against the third instar larvae of the loche Diaphania hyalinata (lepidoptera: pyralidae) screwworm. The application of conidias suspensions of 106 and 1010/ml was evaluated in isolation, registering a mortality on Diaphania hyalinata larvae, between 19% to 68% in the fourth day. As a conclusion the Beauveria bassiana presents a great potential as a microbiological control of Diaphania hyalinata.